Essentials of haematology - Kawthalkar, Shirish M. (Jaypee Brothers Medical Publisher (P) Ltd., 2013)
Second edition presenting common haematologic disorders and blood transfusion, with an emphasis on pathogenesis, diagnosis and treatment.